(untitled) (Medical Forum Monthly, 2026)
Objective: This study evaluated the accuracy of cold and electric pulp tests in defining pulpal status in the Saudi sub-population.Study Design: Cross-sectional analytical studyPlace and Duration of Study: This study was conducted at the College of Dentistry, Qassim University, Saudi Arabia, from September 2023- February 2024.Methods: This cross-sectional study included 118 participants aged 18–60 years with no prior clinical diagnosis of pulpal disease. Pulpal status was determined by the presence (vital) or absence (necrotic) of bleeding from the pulp chamber following access opening. Both cold and electric pulp tests were conducted with at least a 5-minute interval between them. The sensitivity, specificity, and accuracy of each test were evaluated, and reproducibility was measured using the intra class correlation coefficient.Results: The study found that, based on the cold test, 62 (52.5%) teeth were non-vital and 56 (47.5%) were vital. In comparison, the EPT identified 77 (65.3%) teeth as vital and 41 (34.7%) as non-vital. The cold test demonstrated greater diagnostic accuracy (0.808) than the EPT (0.639) in determining pulpal status.Conclusion: The findings indicate that the cold test exhibited higher overall accuracy (80.8%) and specificity (85.5%) than the electric pulp test (63.9% accuracy and 49.1% specificity) in a Saudi sub-population. Although EPTshowed slightly higher sensitivity (77.8% vs. 76.2%), the cold test provided superior predictive values, making it a more dependable method for assessing tooth vitality.